Kualitas Pembelajaran IPA di SMP Negeri 1 Taopa Kabupaten Parigi Moutong - Munifa, Siti; Jamhari, Mohammad; Agni, Raya; Zainal, Syech; Rafiqah, Rafiqah; Alibasyah, Lestari M. P. (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze the quality of science learning at SMP Negeri 1 Taopa. This research used descriptive method with qualitative approach. The subjects of this study consisted of 52 students and 2 science teachers at SMP Negeri 1 Taopa. The types and sources of data used are primary, namely the results of observations, questionnaires and interviews. Based on the results of the study, the quality of learning shows excellent achievements in various aspects. Learning media is in the Very Good category with a percentage of 86.53%, indicating high effectiveness in delivering material. Similarly, the learning method also reached the Very Good category with a percentage of 82.5%, confirming that the combination of media and methods applied was very effective. Furthermore, the learning system also obtained a Very Good category with a percentage of 87.5%, indicating that the flow and structure of learning has been optimally designed. Overall, the findings show that the evaluated learning components contribute significantly to a quality learning experience. Thus, it can be concluded that the quality of learning at SMP Negeri 1 Taopa is in the Very Good category.